Foundations of inclusive education research - Jones, Phyllis; Danforth, Scot. (Bingley, U.K. : Emerald, 2015)
This volume focuses on inquiry into inclusive education from the perspective of scholarly influences in the field of practice and research. A group of key international researchers in the field of inclusive education have each contributed a chapter about a piece of scholarship they believe has influenced inquiry in the field, as a whole.
From special education to integration to genuine inclusion / Scot Danforth, Phyllis Jones -- Developing a critical sociology of special and inclusive education : the contribution of Sally Tomlinson / Sheila Riddell -- Stealth bureaucracy in Sally Tomlinson's irresistible rise of the SEN industry / Julie Allan -- Questioning assumptions : Roger Slee and Julie Allan's reconsideration of inclusive education / Tim Loreman -- Interrupting the prevailing discourse on special education : political and sociological perspectives offered by Len Barton / Phyllis Jones -- The bumpy road to genuinely inclusive schools : still learning from Ferguson's 'rabid' confessions of an authentic inclusionist / S. Anthony Thompson -- New linkages for a complex inclusive education : third world feminism, post-positivist realism and disability studies / Srikala Naraian -- Do attitudes predict behaviour : an (un)solved mystery? / Umesh Sharma, Hasheem Mannan -- Under the mentorship of John Dewey : democratic lessons for inclusive education / Scot Danforth -- Re-imagining inclusive research and practice : a focus on bourdieus concepts of habitus, capital, doxa and field / Joseph Seyram Agbenyega, Sunanta Klibthong -- Assembling all the jigsaw pieces together : the critical work of Dorothy Lipsky and Alan Gartner's Inclusion and school reform / David J. Connor -- Why the pursuit of inclusive education cannot be left to science : lessons from the work of Burton Blatt / Douglas Biklen -- The illusion of our separativeness : exploring Heshusius's concept of participatory consciousness in disability research and inclusive education / Deborah J. Gallagher -- The sociological straitjacket and the ethics of exclusion / Simo Vehmas.
Print version record
Keywords: Education -- Inclusive Education; Teaching of specific groups & persons with special educational needs; Inclusive education -- Research; Mainstreaming in education